Analisis Faktor-Faktor yang Mempengaruhi Perubahan Perilaku Sosial pada Anak yang Aktif dalam Situasi Tertentu: Studi Kasus di Acara Ulang Tahun Kelas - Karimah, Wildanul; Syafrudin, Ulwan; Yulistia, Annisa (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2024)
Social behavior in children is influenced by various internal and external factors, especially in new or specific situations such as social events. This study aims to analyze the factors influencing changes in social behavior in children who are usually active and cheerful but become reserved in certain circumstances. The research was conducted with a qualitative descriptive approach, utilizing interviews with teachers and parents, as well as observations of children's behavior during a birthday event at a kindergarten in Bandar Lampung. The findings reveal that situational factors, such as a noisy environment, unfamiliar social settings, and a lack of emotional support, contribute to the observed behavioral changes. Children who generally exhibit high levels of interaction and enthusiasm in class showed signs of withdrawal, hesitation, and discomfort during the event. The results also indicate the significant role of emotional regulation and social anxiety in shaping children's responses to new situations. This study underscores the importance of early intervention by teachers and parents in fostering emotional resilience and providing a supportive environment for children in social contexts. These findings offer practical insights for educators and caregivers to better understand and address the dynamic nature of children's social behavior in varied settings.